Multiplicação in vitro de Cedrela fissilis Vell. - Amaral, Vanessa Fiad Martins do (2006)
This study had as objective to study the in vitro regeneration of cedar (Cedrela fissilis Vell.), a native tree of economic interest, belonging to Meliaceae family. For seeds desinfestation, different treatments with sodium hypochlorite in different concentration and immersion times were tested combined with differents culture mediums. To establish the nodal segments in vitro, benlate at 300 mg.l-1 and streptomicine sulphate at 10 mg.l-1 were added to the culture medium WPM reduced to ¾ of its salts concentration, isolated or not. After that, the hypocotyl segments from the 30 days in vitro cultured plants were used as explant in sprouts multiplication in culture mediums MS and WPM combined or not with the cytokinins BAP and KIN at 5μM.l-1 . It was also tested, in hypocotyl segments, the influence of BAP (0; 1,25; 2,5 and 5,0 μM.l-1) combined with the IBA or NAA (0,55μM.l- 1), in culture medium WPM during two subcultives. 60 days hypocotyl segments from cultive in BAP (0;1,25; 2,5 and 5,0 μM.l-1) were transferred to WPM medium added of only GA3 at 3μM.l-1 remaining during more than 30 days. Seeds desinfestated with sodium hypochlorite at 2% during 10 minutes showed a lower index of fungal contamination (8,7%) and the higher index of germination (80%), the mediums MS and WPM allowed the germination of 72,5%. The nodal segments from 3 years old plants showed an average index of bacterial contamination (13% 21 days after the inocultation) when cultivated in WPM culture medium added of benlate (300mg.l-1) plus streptomicine sulphate (10 mg.l-1) and survival index of 83%. The explants from the hypocotyl region showed average indexes of regeneration of 2,8 when cultivated in WPM medium supplemented with BAP at 5μM.l-1, on the other hand, in MS medium, the average tax of formation was 2,5 sprouts per explant. When tested in WPM culture medium, in different BAP concentrations, only at 30 days of cultive there was an interaction between the cytokinins doses and the presence of auxins IBA and NAA. BAP at 5μM showed explants with higher taxes of multiplication, regardless the auxins addition to the culture medium. In the following subcultives there was not an interaction between the concentrations and the effect of auxin presence, where the medium without auxin, associated to BAP at 5μM, promoted a higher average of sprouts per explant 2,29 (60 days). The average number of knots at 30 days of cultive was of 2,84 when evaluated the medium with ANA plus 2,5μM of BAP. At 60 days, the culture medium without the auxine promoted an average of 4,15 knots per explant, differing statistically from the mediums with auxin. At 90 days, the number of knots were 5,59 when BAP was used at 5μM plus IBA. The average length of the sprouts in the medium with NAA showed to be the more efficient (0,86 cm) at 30 days of cultive. At 60 days, the average length of the sprouts was of 0,95 and, at 90 days the average length of the sprouts was of 1,14. The formation of callus in the base of the explants happened when cytokinins were added to the medium, and the roots formation happened in the absence of these and in the presence of the auxin, generating complete plants. Explants exposed to GA3 at 60 days of cultive showed a partial reversion, showing an increase in formed roots and average length of the sprouts.